Prenatal exposures and cell type proportions are main drivers of FKBP5 DNA methylation in maltreated and non-maltreated children - Vera N. Karlbauer; Jade Martins; Monika Rex-Haffner; Susann Sauer; Simone Roeh; Katja Dittrich; Peggy Doerr; Heiko Klawitter; Sonja Entringer; Claudia Buss; Sibylle M. Winter; Christine Heim; et al. (Neurobiology of Stress)
DNA methylation in peripheral tissues may be a relevant biomarker of risk for developing mental disorders after exposure to early life adversity. Genes involved in HPA axis regulation, such as FKBP5, might play a key role. In this study, we aimed to identify the main drivers of salivary FKBP5 methylation in a cohort of 162 maltreated and non-maltreated children aged 3–5 years at two measurement timepoints. We combined data from a targeted bisulfite sequencing approach for fine-mapping 49 CpGs in regulatory regions of FKBP5 and epigenetic scores for exposure to alcohol, cigarette smoke, and glucocorticoids derived from the EPICv1 microarray.Most variability of methylation in the FKBP5 locus was explained by estimated cell type proportions as well as epigenetic exposure scores, most prominently by the glucocorticoid exposure score. While not surviving correction for multiple testing, we replicated previously reported associations of FKBP5 methylation with CM. We also detected synergistic effects of both rs1360780 genotype and the glucocorticoid exposure score on FKBP5 hypomethylation. These effects were identified in the 3′TAD, a distal regulatory region of FKBP5 which is not extensively covered in Illumina arrays, emphasizing the need for fine mapping approaches. Additionally, the epigenetic glucocorticoid exposure score was associated with childhood maltreatment, maternal mental disorders, and pregnancy complications, thereby highlighting the role of glucocorticoid signaling in the epigenetic consequences of early adversity.These results underscore the need to assess cell type heterogeneity in targeted assessments of DNA methylation and show the impact of exposures beyond just childhood maltreatment such as glucocorticoid exposure.